Environmental Impact Related with People Management - Lopes, Albino Anjos; Romana, Fernando Acabado (Archives of Business Research, 2023)
In this text we begin by presenting the relationship between Art and Science, with regard to the production and conservation of life, in the context of developed societies of the 21st century, seen as two faces of the research of a reality, extremely complex, but that almost all aim to reduce to a simplistic equation. Despite all the climate summits that have taken place (we are going to the 26th), without any real solutions being reached as effective solutions for the future, there does not even seem to be a clear awareness of the circumstances that have led the world to a situation of emergency. That is why we sought to place the climate issue in the context of a revolution according to the principles of the paradigm of the decisive importance of small groups, of small initiatives, that is, of the “lean” philosophy for agriculture, which accompanied (and surpassed) the the “lean” revolution that took place in the industry in the early 1970s. It should be remembered that this was the precise moment when the first warnings from the “Club de Roma” were heard, about the limits to growth and the predictable depletion of resources, as well as as well as the need to reverse the path of increasing waste. Finally, we consider that this “coincidence of divergence” between the paradigms of agriculture (still deeply anchored in the productivism of a primary Taylorism) and that of industry (conceived, however, from the notion of team and organization in a network of small businesses, as well as an ability to work collaboratively), may not be the result of mere chance. Carvalho and Cardoso (2010), in a well-documented article, discuss, based on a literature review, the relationship between people management and art. The authors support and support our position on the need for intuition (support of imagination, sensitivity and skill) in the management of human creativity, as we have defended in our works (Lopes and Picado, 2010). Organizations open to the ambitions of art are better able to pursue multiple (non-hierarchical) goals, based on fluid and “semi-connected” technologies, as James March and Karl Weick teach, following John Dewey.